EFFECTIVENESS OF A SCHOOL-BASED EDUCATIONAL INTERVENTION IN IMPROVING FIRST AID COMPETENCY FOR INJURY MANAGEMENT AMONG SCHOOLCHILDREN - Rufaida Nur Fitriana; Erlina Windyastuti; Hanugrah Ardya Crisdian Saraswati; Rolando Rahardjoputro (Jurnal Kesehatan Kusuma Husada, 2026)
Background: Childhood injuries remain a leading public health concern worldwide and frequently occur in school environments. The ability to provide appropriate first aid immediately after an injury is essential for reducing complications and improving recovery outcomes. This study investigated the effectiveness of a structured, school-based educational intervention in improving first-aid competency among elementary school students.Methods: A quasi-experimental study employing a pretest-posttest nonequivalent control group design was conducted among 144 elementary school students selected through purposive sampling. Participants were allocated into an intervention group (n = 72) and a control group (n = 72). Students in the intervention group received a structured first aid education program delivered over three consecutive days using a validated learning module, while the control group continued routine school health activities. First aid competency was assessed before and after the intervention using a validated questionnaire. Data were analyzed using paired-samples and independent-samples t-tests, with statistical significance established at p < 0.05.Results: The intervention and control groups demonstrated comparable baseline competency scores prior to the educational program. Following the intervention, the intervention group exhibited a marked improvement in first aid competency, whereas no meaningful change was observed among students in the control group. Comparative analysis confirmed that post-intervention competency scores were significantly higher in the intervention group than in the control group (p < 0.001).Conclusion: Educational programs in schools effectively enhance children's skills in providing first aid for injuries.